The Undercurrent - Grant, Robert, 1852-1940; Yohn, F. C. (Frederick Coffay), 1875-1933 (Salt Lake City, UT : Project Gutenberg, 2018)
"The Undercurrent" by Robert Grant is a novel written in the early 20th century. The book explores the complexities of love, ambition, and societal expectations through the story of Constance Forbes, a young woman who marries Emil Stuart, a man striving for success in a rapidly growing city. As they navigate their relationship and their individual ambitions, the story delves into themes of disillusionment and the challenges faced in a changing societal landscape. The opening of the narrative presents the wedding of Constance and Emil, highlighting Constance's mixed feelings about her choice to marry, reflecting on the sacrifices she makes for love and her aspirations in the field of education. The couple's dynamic is established through their conversation and interactions, revealing Emil's ambition and Constance's support as they settle into married life. However, as Emil confronts the harsh realities of business and eventually faces failure, the strain on their relationship becomes apparent, setting the stage for deeper conflicts around personal aspirations and societal pressures. This beginning hints at the tumultuous journey the couple will face as they grapple with their dreams and the realities of life together. (This is an automatically generated summary.)
Release date is 2018-01-04
Produced by Al Haines
Keywords: Married people -- Fiction; Rich people -- Fiction; Divorce -- Fiction; American fiction -- 20th century